Limited Information Shared Control and its Applications to Large Vehicle Manipulators - Varga, Bálint (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2024)
This work focuses on the Limited Information Shared Control and its controller design using potential games. Through the developed systematic controller design, the experiments demonstrate the effectiveness and superiority of this concept compared to traditional manual and non-cooperative control approaches in the application of large vehicle manipulators.